Application of Printable ITO/PEDOT Nanocomposites as Transparent Electrodes in Optoelectronic Devices - Maksimenko, Ilja; Kilian, Daniel; Mehringer, Christian; Voigt, Michael; Peukert, Wolfgang; Wellmann, Peter (Conference on Lasers and Electro-Optics, 2012)
Printable transparent hybrid composites consisting of indium tin oxide (ITO) nanoparticles and conducting polymer 3,4-polyethylenedioxythiophene: polystyrene sulfonic acid (PEDOT:PSS)) as matrix material were developed and used as transparent electrodes in all-printed flexible electroluminescent lamps and electrochromic display
Keywords: optical devices; electro-optical devices; thin films; transparent conductive coatings

Electrical properties of solution processed layers based on Ge-Si alloy nanoparticles - Meric, Zeynep; Mehringer, Christian; Jank, Michael. P. M.; Peukert, Wolfgang; Frey, Lothar (MRS Advances, 2016)
Ge-Si alloy nanoparticles (NPs) covering the full range of compositions were studied in regard to their suitability as semiconducting channel layer in thin-film transistors (TFTs). Special focus is given to the influence of annealing and encapsulation techniques on the contact and channel properties. Therefore, electrical characterization methods separating contact from channel characteristics are highlighted and applied. It is demonstrated that appropriate passivation of the nanoparticle surfaces can improve the Ion/Ioff ratios by modulation of the density of free charge carriers and also can suppress hysteresis effects. Ge-rich NP alloys can generally be passivated more effectively regardless if passivation is done with solution-processed poly(methyl methacrylate) (PMMA) or by aluminum oxide (Al2O3) from Atomic Layer Deposition (ALD). Sufficient annealing improves the contact formation between aluminum electrodes and Ge-Si particles by modification of charge injection. The presented analysis leads to a better understanding interface and surface effects in porous nanoparticle semiconductors for application in TFT devices.
Keywords: thin film; passivation; nanostructure

Fabrication, charge carrier transport, and application of printable nanocomposites based on indium tin oxide nanoparticles and conducting polymer 3,4-ethylenedioxythiophene/polystyrene sulfonic acid - Maksimenko, Ilja; Kilian, Daniel; Mehringer, Christian; Voigt, Michael; Peukert, Wolfgang; Wellmann, Peter (Journal of Applied Physics, 2011)
Printable transparent hybrid composites consisting of indium tin oxide (In2O3:Sn; ITO) nanoparticles and conducting polymer 3,4-polyethylenedioxythiophene (PEDOT) as matrix material were developed. The basic idea is to fill up the pores of the highly porous nanoparticulate ITO network to improve the interparticle contact and hence the conductivity of printed ITO thin films. Ready-to-use and stable aqueous dispersions were fabricated starting from ITO nanoparticles and aqueous formulation of conducting PEDOT and polystyrene sulfonic acid (PSS). This report presents and discusses key factors to obtain stable ITO-PEDOT dispersions with different mixing ratios and their application for printable devices as transparent electrode material. It was found that the f-potential value is crucial for preparation of stable dispersions. Electrical and optical properties of the hybrid ITO-PEDOT coatings were analyzed. Temperature dependent resistivity measurements reveal that conduction occurs by fluctuation induced tunneling. Transparent and conducting nanocomposite layers with a conductivity as high as 132 X1cm1 were fabricated by a low-temperature (T¼130 C) and entirely vacuum-free process. An all-printed electroluminescent lamp on a flexible substrate was realized as a demonstrator showing the applicability of such coatings for voltage-driven optoelectronic devices.<br

Gas phase synthesis of anisotropic silicon germanium hybrid nanoparticles - Mehringer, Christian; Wagner, Richard; Jakuttis, Thomas; Butz, Benjamin; Spiecker, Erdmann; Peukert, Wolfgang (Journal of Aerosol Science, 2014)
We demonstrate the capability of hot wall reactor gas phase synthesis to produce germanium (Ge) on silicon (Si) anisotropic particles. A two stage reactor setup is used to produce silicon nanoparticles (SiNPs) of 29.6 nm in diameter with a very narrow size distribution and to deposit Ge on them. The gaseous precursors are monosilane (SiH4) and monogermane (GeH4). In a SEM study Ge patch formation on the SiNPs due to Stranski–Krastanov growth is observed. The patch size as well as the number of patches per SiNP is dependent on the process temperature and the GeH4 partial pressure. By varying these parameters it is possible to synthesize Janus-like particles with only one e.g. facetted Ge patch per SiNP, as well as patchy particles carrying an average of four to eight patches. HRTEM analysis shows, that the Ge grows epitaxial and crystalline on the surface of the SiNPs. From geometric phase analysis (GPA) the termination of inserted (220) half planes corresponding to misfit dislocations can be deduced, indicating a largely relaxed lattice in the Ge patches. A continuous tilt of the (111) lattice planes in the Si core below a Ge patch indicates that elastic deformation also contributes to the strain relaxation.

Germanium-silicon alloy and core-shell nanocrystals by gas phase synthesis - Mehringer, Christian; Kloner, Christian; Butz, Benjamin; Winter, Benjamin; Spiecker, Erdmann; Peukert, Wolfgang (Nanoscale, 2015)
In this work we present a novel route to synthesize well defined germanium-silicon alloy (GexSi1-x) and core-shell nanocrystals (NCs) employing monosilane (SiH4) and monogermane (GeH4) as precursors in a continuously operated two-stage hot-wall aerosol reactor setup. The first hot-wall reactor stage (HWR I) is used to produce silicon (Si) seed particles from SiH4 pyrolysis in Argon (Ar). The resulting seeding aerosol is fed into the second reactor stage (HWR II) and a mixture of SiH4 and GeH4 is added. The ratio of the precursors in the feed, their partial pressures, the synthesis temperature in HWR II and the overall pressure are varied depending on the desired morphology and composition. Alloy particle production is achieved in the heterogeneous surface reaction regime, meaning that germanium (Ge) and Si are deposited on the seed surface simultaneously. The NCs can be synthesized with any desired composition, whilst maintaining a mean diameter around 30 nm with a geometric standard deviation (GSD) around 1.25. The absorption behavior and the related fundamental optical band gap energy in dependence on the alloy composition are exemplarily presented. They prove the possibility to tailor NC properties for electronical and opto-electronical applications. In the homogeneous gas phase reaction regime facetted Ge-Si core-shell structures are accessible. The Ge deposition on the seeds precedes the Si deposition due to different gas phase reaction kinetics of the precursors. The Si layer grows epitaxially on the Ge core and is around 5 nm thick.

Tunable conduction type of solution-processed germanium nanoparticle based field effect transistors and their inverter integration - Peukert, Wolfgang; Meric, Zeynep; Mehringer, Christian; Jank, Michael; Frey, Lothar; Karpstein, Nicolas (Physical Chemistry Chemical Physics, 2015)
In this work we demonstrate the fabrication of germanium nanoparticle (NP) based electronics. The whole process chain from the nanoparticle production up to the point of inverter integration is covered. Ge NPs with a mean diameter of 33 nm and a geometric standard deviation of 1.19 are synthesized in the gas phase by thermal decomposition of GeH4 precursor in a seeded growth process. Dispersions of these particles in ethanol are employed to fabricate thin particulate films (60 to 120 nm in thickness) on substrates with a pre-patterned interdigitated aluminum electrode structure. The effect of temperature treatment, polymethyl methacrylate encapsulation and alumina coating by plasma-assisted atomic layer deposition (employing various temperatures) on the performance of these layers as thin film transistors (TFTs) is investigated. This coating combined with thermal annealing delivers ambipolar TFTs which show an Ion/Ioff ratio in the range of 102. We report fabrication of n-type, p-type or ambipolar Ge NP TFTs at maximum temperatures of 450 °C. For the first time, a circuit using two ambipolar TFTs is demonstrated to function as a NOT gate with an inverter gain of up to 4 which can be operated at room temperature in ambient ai
Keywords: nanoparticle; electronic; thermal; decomposition; growth; particulate; film